Twelve Weeks of Combined Resistance and Aerobic Exercise Improves Cardiometabolic Biomarkers and Enhances Red Blood Cell Hemorheological Function in Obese Older Men: A Randomized Controlled Trial - Kim, Sung-Woo (Int J Environ Res Public Health, 2019)
The present study examined the effect of a 12-week combined resistance and aerobic exercise training program on cardiometabolic biomarkers and red blood cell (RBC) hemorheological function in 20 obese older men (mean age: 68.8 ± 0.9 years). Subjects were randomly divided into two groups (exercise intervention [EXP; n = 10] and control [CON; n = 10]). The EXP subjects performed resistance and aerobic exercise training program three times per week for 12 weeks, and the CON subjects maintained their regular lifestyle during the intervention period. Body composition was estimated using bioelectrical impedance analysis equipment. Cardiometabolic biomarkers (glucose, insulin, homeostasis model assessment-estimated insulin resistance (HOMA-IR), HOMA β-cell function, and leptin) and RBC hemorheological parameters (RBC deformability and aggregation) were analyzed. Percent body fat decreased significantly in the EXP group during the intervention period but increased significantly in the CON group. Insulin increased significantly in the CON group over the 12-week period and both insulin and HOMA-IR were significantly higher in the CON group than in the EXP group at post-test. RBC deformability (RBC EI_3Pa) and aggregation (RBC AI_3Pa) improved significantly only in the EXP group. The present study suggests that combined exercise training can be useful for improving cardiometabolic biomarkers and RBC hemorheological parameters in obese older men and may help prevent metabolic syndrome and cardiovascular diseases.